2016
DOI: 10.1080/17436753.2016.1163006
|View full text |Cite
|
Sign up to set email alerts
|

Calcium silicate/calcium aluminate composite biocement for bone restorative application: synthesis, characterisation andin vitrobiocompatibility

Abstract: Pure β-dicalcium silicate and monocalcium aluminate powder were prepared by Pechini method. A series of calcium silicate/calcium aluminate cements (CSC/CAC) were prepared. The setting time, crystalline phases, microstructures, compressive strength, cells attachment and silicon release of the cements were investigated. The results indicate that the setting time of CSC/CAC was shorter than that of either CSC or CAC. The hydration products in CSC/CAC composite are gehlenite (Ca 2 Al 2 SiO 7 •8H 2 O), calcium alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, for clinical applications, bone-grafting materials are required to provide adequate mechanical support for the defect site [26]. Although the compressive strength of the composite cements showed a slightly decrease, it was similar to that of cancellous bone (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) [27] and therefore still showed suitable for clinical applications. The present study provides understanding of how the compressive strength of composite cement changes with MCP content and it could help researchers to optimise compressive strength in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for clinical applications, bone-grafting materials are required to provide adequate mechanical support for the defect site [26]. Although the compressive strength of the composite cements showed a slightly decrease, it was similar to that of cancellous bone (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) [27] and therefore still showed suitable for clinical applications. The present study provides understanding of how the compressive strength of composite cement changes with MCP content and it could help researchers to optimise compressive strength in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Biological characteristics of new CSbased materials have been optimised by adding additional components such as setting modulators, radiopacifying agents and drugs [10]. Recently, the application of CS in bone repair has drawn more interest [11], since it shows self-setting properties at body temperature, high mouldability, excellent bioactivity and osteostimulatory and biodegradable properties [12][13][14]. It has also been shown that silicon (Si) ions released from CS could provide an ideal extracellular environment for directing osteogenic differentiation of bone mesenchymal stem cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…At body temperature, the hydration reactions may be written as in Equations ( 6) and (7) The calcium aluminate cements also create a high pH environment and release calcium ions, 106 which are prerequisites for bioactivity, albeit these cements are not as alkaline as the calcium silicate cements. 107 Some investigators have combined the calcium aluminate cements or silica with calcium silicate cements [108][109][110] for use in dentistry. Presumably, the goal is to combine silicate ion release for osteogenesis and the benefits of the calcium aluminate cement for acid resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium silicate and calcium silicate/aluminate cements have been evaluated for bone cements. 108,133,298,299 Dental and bone cements need the same biocompatibility properties, preferably including osteogenesis for bone deficiencies. Bone cements require injectability, similar to root canal sealers.…”
Section: Uses For Calcium Siicate and Calcium Aluminate Cementsmentioning
confidence: 99%
“…Previous studies have demonstrated that Ca 2 Al 2 SiO 7 could release trace bioactive ions (e.g., Ca 2+ and Si 4+ ) in tissue microenvironment, which favored the bone tissue regeneration. [24][25][26][27][28][29][30][31][32] Moreover, it was found that Ca 2 Al 2 SiO 7 has a very good self-forming ability of pores during sintering process, 33 and the rough and porous surface has important effect on cell behavior and tissue regeneration. [34][35][36][37] In addition, during the heat treatment of SiC-containing ceramics, CO gas bubbles resulted from the oxidation of SiC also favored the formation of porous SiO 2 [38][39][40] and the final porous Ca 2 Al 2 SiO 7 coating.…”
Section: Introductionmentioning
confidence: 99%